PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN KOMPETENSI MAHASISWA PGSD MENGGUNAKAN FITUR F-LEARN ASSIGMENT DAN FORUM - Astuti, Suhandi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
Learning using the Flearn LMS in the PGSD Study Program at Satya Wacana Christian University has been a common practice since 2011. However, to ensure the effectiveness of Flearn, research needs to be conducted. Therefore, this study aims to: 1) determine the development level of students' critical thinking abilities in learning using Flearn, 2) determine the improvement level of student learning outcomes in learning using Flearn, and 3) determine the relationship between students' critical thinking abilities and their learning outcomes. The type of research is a collaborative action research. The action taken involves the implementation of the  assignment and forum features in FLearn. The participants in this study involved 60 students. The research instrument uses test questions to measure student learning outcome variables and a rubric of critical thinking abilities to measure the level of students' critical thinking abilities. The data analysis techniques used percentage descriptive techniques and correlation tests. The results of the study indicate that the use of Flearn through assignment and forum features can develop students' critical thinking abilities in the critical category. Meanwhile, student learning outcomes are in the high category. However, no significant positive relationship was found between students' critical thinking abilities and their learning outcomes. Based on the aforementioned findings, it is advisable for the managers of the PGSD study program to support and encourage instructors to actively include Flearn methodology into their lectures. To utilize the assignment and forum functionalities of the Flearn LMS for their lectures, lecturers are required.